Postmodernity as secularization process of the Christian Logos - Zacarias, William Felipe; Westphal, Euler Renato (Vox Scripturae - Revista Teológica Internacional, 2016)
The Postmodernity is a problem and a challenge for Christian theology. The Eschatology was diluted at the moment and the reference to the construction of the web of meanings of human life are transferred to the immanent world. The Nihilism has become on a dogma, based on the “eternal return of the same” of Friedrich Nietzsche. The ultimate cause of this thinking is the hedonism that culminates in an orgiastic culture, violent and post-human. Postmodernity, by breaking with the vision of the Judeo-Christian world, also broke with what until then was the West inexorably. This disruption means a return to the era tragic of the Greeks that saw the differences between people. The Christianity, on the contrary, gave equal rights to all people, regardless of the apparent accidents that differentiate them. Gianni Vattimo proposes the kenosis from Philippians 2.5-7 as an attempt to save Christianity from your end. However, from the theological point of view, its proposal is insufficient to cover only a part of Christology. Therefore, without the Judeo-Christian world vision, the western humanity, beauty and history collapses.